Continuing the Conversation About Comparative Ethics. Issue 3 (September 2015) - Sachedina, Abdulaziz
Abstract This essay clarifies my stance on the distinctive facets of Christianity as a sole paradigm for a liberal interpretation of Islam in the area of human rights. It attempts to demonstrate the limits of applying a comparative ethics methodology without a firm grounding in historical studies that reveal the contextual aspects of the debate whether any religion, including Islam, is incapable of providing cultural legitimacy to the secular Universal Declaration of Human Rights among Muslim traditionalists. In the absence of the "Church, " Islam has congruent scriptural resources to offer a distinctly enhanced system that works as an alternative to the uncritical secularization of moral‐spiritual scriptural resources. Critical evaluation of the political history of Christianity and Islam reveals internal hermeneutical dynamics that lead to accommodation with the demands of secularization to advance human rights across cultures and nations.